Understanding and Optimizing Oxygen Plasma Treatment for Enhanced Cu-Cu Bonding Application - Sangwoo Park; Sangmin Lee; Junyoung Choi; Sarah Eunkyung Kim (IEEE Access)
This study investigates the optimization of O2 plasma treatment conditions to enhance Cu-Cu bonding. The O2 plasma treatment conditions were optimized using Design of Experiments (DOE), adjusting three parameters: O2 flow rate, plasma power, and treatment time, to minimize oxidation while maximizing surface energy. X-ray photoelectron spectroscopy (XPS) was employed to calculate the Cu atomic percentage (at%) at the surface and at a depth of 25 seconds of etching, while water contact angle (WCA) measurements assessed surface energy. The results indicated that decreasing the O2 flow rate reduced oxidation without significantly impacting surface energy. Plasma power and treatment time were optimized through a balanced approach. The identified optimal conditions were an O2 flow rate of 50 sccm, plasma power of 50 W, and a process time of 20 seconds. Subsequent SEM analysis confirmed a wavy bonding interface indicative of strong Cu diffusion bonding, resulting in approximately a 40% increase in shear strength. The findings suggest that controlled O2 plasma treatment effectively enhances bonding strength, providing direction for the optimization of O2 plasma for Cu bonding in advanced packaging technologies and hybrid bonding applications.